Right cerebral hemisphere and central auditory processing in children with developmental dyslexia - Paulina C. Murphy-Ruiz; Yolanda R. Penaloza-Lopez; Felipe Garcia-Pedroza; Adrian Poblano (Arquivos de Neuro-Psiquiatria)
Objective We hypothesized that if the right hemisphere auditory processing abilities can be altered in children with developmental dyslexia (DD), we can detect dysfunction using specific tests. Method We performed an analytical comparative cross-sectional study. We studied 20 right-handed children with DD and 20 healthy right-handed control subjects (CS). Children in both groups were age, gender, and school-grade matched. Focusing on the right hemisphere’s contribution, we utilized tests to measure alterations in central auditory processing (CAP), such as determination of frequency patterns; sound duration; music pitch recognition; and identification of environmental sounds. We compared results among the two groups. Results Children with DD showed lower performance than CS in all CAP subtests, including those that preferentially engaged the cerebral right hemisphere. Conclusion Our data suggests a significant contribution of the right hemisphere in alterations of CAP in children with DD. Thus, right hemisphere CAP must be considered for examination and rehabilitation of children with DD.